"They Were Built to Last": Anticonsumption and the Materiality of Waste in Obsolete Buildings. (November 2018) - Anderson, Stephanie; Hamilton, Kathy; Tonner, Andrea
Previous consumer research on waste has prioritized disposable and low-involvement possessions. The authors extend scholarship into the context of obsolete buildings to better engage with the complex materiality of waste and to explore the role anticonsumption plays in consumers' valuations of end-stage consumption. This study focuses on the phenomenon of urban exploration, a subculture that seeks to discover and explore derelict buildings. Drawing on an ethnographic study including in-depth interviews, the authors reveal how anticonsumption manifests in the urban environment in terms of alternative understandings of value. In contrast to the economic valuations that often dominate public policy decision making, this study highlights the need for policy makers to consider diverse, and perhaps conflicting, value regimes. The authors propose an Obsolescence Impact Evaluation that enables a systematic assessment of the stakeholders potentially affected by redevelopment and/or demolition, differing regimes of valuation relevant to these outcomes, and potential uses of the buildings. The authors suggest various ways that public policy makers can take advantage of this tool.